The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1471-0528.2006.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Third‐trimester fetal MRI in isolated 10‐ to 12‐mm ventriculomegaly: is it worth it?

Abstract: Objective The justification for magnetic resonance imaging (MRI) in isolated mild ventriculomegaly remains controversial. This study was undertaken to evaluate the contribution of third-trimester MRI in isolated 10-to 12-mm fetal ventriculomegaly.Design Observational prospective cohort study.Setting Universitary prenatal reference centre.Population From February 2000 to May 2005, we prospectively collected data concerning fetuses referred to us for cerebral MRI following detection of ventriculomegaly by ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
4
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 26 publications
6
66
4
1
Order By: Relevance
“…Early work by Garel and Alberti 17 seemed to support that assumption, but a more recent publication, including the same author, showed the opposite conclusion. 18 The retrospective analysis of Salomon et al 18 included 185 thirdtrimester fetuses who had isolated mild VM (ie, 10-to 12-mm trigones) as measured on sonography. They found that the most frequent disagreement between sonography and iuMR was in the classification of the degree of VM.…”
Section: Discussionmentioning
confidence: 99%
“…Early work by Garel and Alberti 17 seemed to support that assumption, but a more recent publication, including the same author, showed the opposite conclusion. 18 The retrospective analysis of Salomon et al 18 included 185 thirdtrimester fetuses who had isolated mild VM (ie, 10-to 12-mm trigones) as measured on sonography. They found that the most frequent disagreement between sonography and iuMR was in the classification of the degree of VM.…”
Section: Discussionmentioning
confidence: 99%
“…The value of in utero MRI in cases of ultrasound diagnosed fetal isolated VM is addressed by a number of recent studies (Malinger et al, 2004;Valsky et al, 2004;Ouahba et al, 2006;Salomon et al, 2006;Benacerraf et al, 2007;Glenn and Barkovich, 2006a;Glenn and Barkovich, 2006b;Morris et al, 2007). The percentage of additional abnormalities diagnosed by MRI ranges from 5% (Salomon et al, 2006) to 50% (Morris et al, 2007).…”
Section: Structural Malformationsmentioning
confidence: 99%
“…VM is severe when the measurement of the ventricular width is >15 mm, or ≥15 mm according to different authors (Den Hollander et al, 1998;Graham et al, 2001;Gaglioti et al, 2005;Breeze et al, 2007); it is defined mild or borderline when the measurement is less (Wax et al, 2003;Wyldes and Watkinson, 2004). Recent data would suggest to further divide borderline VM into mild (10-12 mm) and moderate (>12-15 mm) (Signorelli et al, 2004;Gaglioti et al, 2005;Salomon et al, 2006;Falip et al, 2007).…”
Section: Prenatal Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of magnetic resonance imaging (MRI) has been advocated as a useful tool in evaluating fetuses with mild VM [2,19,22,26]; it adds important information in 6%-10% of the cases, particularly in recognizing associated cortical anomalies. For this reason the appropriate time to perform MRI is in the third trimester; it must be done by experienced operators in reference centers, following an accurate neurosonography in order to avoid useless request of such a sophisticated and expansive procedure.…”
Section: Ruling Out For Associated Anomaliesmentioning
confidence: 99%